Moving toward sustainable environment: the effects of hydropower industry on water quality in EU economies - Mohd Alsaleh; A. S., Abdul Rahim (Sage Publications, 2022)
This research investigates the effect of hydropower yields on water quality in European Union participating nations from 1990 to 2019. Integrating the panel fully modified ordinary least squares, the outcomes show that water quality degradation increase with a rise in hydropower production growth. Similarly, fossil fuel, economic growth and population density are found to be increasing water resource pollution. While institutional quality is found to decrease water quality degradation and water resource pollution. The finding implies that water quality degradation in the EU27 region can be effectively increased by increasing the amount of hydropower production in sustainability procedures. This will increasingly influence the status of climate change. The evaluated outcomes are observed to be valid as they were authenticated with the panel dynamic ordinary least square and pooled ordinary least square. Therefore, it attests to the paper's uniqueness, input to the body of knowledge and novelty. The research suggests that for EU27 nations have to enhance the role of the hydropower industry in their energy mix to achieve Energy Union objectives taking into consideration the water resources pollution factor. Authorities in these nations must also focus more on investing in the growth of the hydropower industry to add more to its production and availability of renewable energy and decrease water quality degradation. The government of these nations can similarly stress the competence and sustainability of hydropower production and water resource conservation to reach energy security and reduce water quality degradation.